Stereotypical Representations of Women's Bodies and Voices in Kim Ji-Yeong's Novel, Born 1982 and Implications for Learning Indonesian - Divany Nurcholifah Ekasaputri Bami; Sayama Malabar; La Ode Gusman Nasiru (Raja Zulkarnain Education Foundation, 2025)
This study aims to describe the stereotypical representation of women’s bodies and voices in the domestic and public spheres in the novel Kim Ji-Yeong, Born 1982 by Cho Nam-Joo using Helene Cixous’s écriture féminine theory, its relevance to contemporary women’s representation, and its implications for Indonesian language learning in schools. This is a qualitative research with descriptive analysis method. The data source is the novel Kim Ji-Yeong, Born 1982. The data consist of excerpts from stories, dialogues, scenes, and descriptions containing stereotypical representations of women’s bodies and voices. Data collection techniques use reading and note-taking techniques. Data were analyzed by identifying, classifying, analyzing, interpreting, and concluding. The research findings show that stereotypical representations are divided into three aspects of écriture féminine: language and deconstruction (31 data) displaying the silencing of women’s voices, body and sexuality (12 data) showing the reduction of women’s bodies as reproductive tools and objects of violence, and motherhood (5 data) depicting motherhood as chains that bind women. Cho Nam-Joo practices écriture féminine by honestly writing about women’s bodily experiences and voices as a form of resistance against patriarchal language domination. The relevance to contemporary conditions includes the practice of son preference, domestic patriarchy and double burden, and reproductive coercion that still occur in Indonesia. The novel can be used as teaching material for Grade XII Phase F of the Merdeka Curriculum to develop critical literacy and achieve the Pancasila Student Profile dimensions of critical reasoning and global diversity, as well as create transformative learning.